Analisis Perspektif Maslahah terhadap Keputusan Pemerintah terkait Pelegalan Alat Kontrasepsi di Indonesia - Wathoni, M. Naufal Addil; Mutawali, Muhammad; Indrawati, Teti (STAINI Press, 2025)
This study analyzes government policies related to the legalization of contraceptives through the maslahah theory, where the government recently legalized contraceptives in Indonesia for school teenagers in Indonesia. This theory examines how the benefits and harms are contained in government policies related to the legalization of contraceptives in Indonesia. As we know that contraceptives function as a means of preventing pregnancy among married couples who hold the concept of family planning. This study uses a literature study approach, where data and documentation are taken from books, articles, journals, research report notes from previous researchers. This study also uses a normative legal research method with a literature study approach. The main sources include classical and contemporary fiqh books, journal articles, and legal reports. This study identifies that this legalization has two dimensions of maslahah: al-mursalah for married couples, meaning that contraceptives for married couples have benefits, namely as a means of preventing pregnancy and al-mulghah for unmarried adolescent users, meaning that if an unmarried couple uses contraceptives to have sex like a husband and wife, it is still counted as an act of adultery. This research offers a new perspective in understanding the relationship between public policy and maqasid sharia.